Lifelines as a Tool to Predict Death - Sneha.S1, Aswath2, Priyadarshee Pradhan3, P. Sampath Kumar4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The study of the relative positions of astronomical objects and their movements is called Astrology. It is used as a means for deriving information about terrestrial planets and affairs of humans. The fear of the unknown is the primary reason for the current fascination with horoscopes. The beliefs are different among different cultures and every country has their own belief systems. Some of the beliefs and superstitions of Indians are seen to have been passed on from generation to generation. The Aim of the study is to co-relate the death with life line. Plotting the data against the age for correlation in scattered diagram it was observed that it did not reflect the life span of the individuals. Though people have belief in different aspects of astrology, this study proves that the there is no scientific basis to the claims of palmistry.